2017
DOI: 10.3390/ijns3010001
|View full text |Cite
|
Sign up to set email alerts
|

Neonatal Screening for Primary Carnitine Deficiency: Lessons Learned from the Faroe Islands

Abstract: Primary carnitine deficiency is caused by the defective OCTN2 carnitine transporter encoded by the SLC22A5 gene. A lack of carnitine impairs fatty acid oxidation resulting in hypoketotic hypoglycemia, hepatic encephalopathy, skeletal and cardiac myopathy, and arrhythmia. This condition can be detected by finding low levels of free carnitine (C0) in neonatal screening. Mothers with primary carnitine deficiency can also be identified by low carnitine levels in their infant by newborn screening. Primary carnitine… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 37 publications
0
8
0
Order By: Relevance
“…The diagnosis can therefore be missed if screening is performed too close to birth and no second screening is obtained. In the Faroe Islands, post‐neonatal screening (age > 2 months) was able to identify additional patients who had unrevealing newborn screening, confirming that patients with primary carnitine deficiency are missed by current newborn screening methods (Steuerwald et al., ). For these reasons, primary carnitine deficiency should be considered in children and adults with a suitable clinical presentation (hypoglycemia, cardiomyopathy, arrhythmia, sudden death) even in the presence of a normal newborn screening test.…”
Section: Discussionmentioning
confidence: 65%
See 1 more Smart Citation
“…The diagnosis can therefore be missed if screening is performed too close to birth and no second screening is obtained. In the Faroe Islands, post‐neonatal screening (age > 2 months) was able to identify additional patients who had unrevealing newborn screening, confirming that patients with primary carnitine deficiency are missed by current newborn screening methods (Steuerwald et al., ). For these reasons, primary carnitine deficiency should be considered in children and adults with a suitable clinical presentation (hypoglycemia, cardiomyopathy, arrhythmia, sudden death) even in the presence of a normal newborn screening test.…”
Section: Discussionmentioning
confidence: 65%
“…The incidence of primary carnitine deficiency varies with a frequency of approximately 1:40,000 newborns in Japan, 1:37,000–1:100,000 newborns in Australia, and 1:142,000 in the USA (Koizumi et al., ; Longo et al., ; Therrell, Lloyd‐Puryear, Camp, & Mann, ; Wilcken, Wiley, Hammond, & Carpenter, ). The highest incidence of primary carnitine deficiency (1:300) is in the Faroe Islands, an archipelago in the North Atlantic that remained geographically isolated for many centuries, where about 5% of the population is carrier for an abnormal allele (Longo et al., ; Rasmussen et al., ; Rasmussen, Kober, Lund, & Nielsen, ; Steuerwald et al., ).…”
Section: Introductionmentioning
confidence: 99%
“…Data from the Region 4 Stork collaborative project also show that a large proportion of patients with PCD exhibit C0 levels in their first newborn screening sample above the standard cut-offs that apply for low C0 in newborn screening [22]. A study conducted in the Faroe Islands revealed that post-neonatal screening beyond 2 months of age successfully identified additional affected patients whose newborn screening results had been unremarkable [23]. The low sensitivity and specificity of newborn screening for PCD and the numerous asymptomatic mothers identified makes including PCD generally within newborn screening programmes controversial [8].…”
Section: Discussionmentioning
confidence: 99%
“…The estimated incidence of PCD is 1:40,000–1:142,000 based on the results of newborn screening (Koizumi et al, ; Magoulas & El‐Hattab, ; Therrell, Lloyd‐Puryear, Camp, & Mann, ; Wilcken, Wiley, Hammond, & Carpenter, ). In certain areas, such as the Faroe Islands, PCD is a common disease with an incidence of 1:300 (Rasmussen, Kober, Lund, & Nielsen, ; Steuerwald et al, ). The incidence of PCD in China is approximately 1:8,938–45,000 among diverse regions (Han et al, , ; Ma, ; Sun, Wang, & Jiang, ); this range is influenced by when and where the epidemiological data were collected.…”
Section: Introductionmentioning
confidence: 99%